Factores de riesgo asociados a úlceras de presión en pacientes con estancia prolongada atendidos en el Hospital Belén de Trujillo - Rodas Rodríguez, María Cristina (2014)
To identify risk factors associated with pressure ulcers in patients with prolonged stay treated in Belen Trujillo Hospital. Material and Methods: Analytical, observational, retrospective, case-control study type. The study population consisted of 80 patients established criteria of inclusion and exclusion, and distributed into two groups: with and without development of pressure ulcers. Results: The statistical analysis of the study variables was compared sex(OR: 3.5,p<0.05), hypotension(OR: 1, p>0.05), hypoalbuminemia (OR: 1, p <0.05), age (OR: 3.5,p<0.05), obesity (OR: 1.79, p> 0.05) and chronic diseases(OR: 1.35, p> 0.05). Conclusions: Age, male sex and hypoalbuminemia were risk factors for the development of ulcers pressure. The pressure, obesity and comorbidities were not risk factors for development of pressure ulcers